2020
DOI: 10.1016/j.molcel.2020.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical-Grade Rigosertib Is a Microtubule-Destabilizing Agent

Abstract: Highlights d Pharmaceutical-grade rigosertib kills cells by destabilizing microtubules d Pharmaceutical-grade rigosertib destabilizes microtubules in cells and in vitro d A rigosertib-binding mutation in tubulin alleviates rigosertibmediated toxicity

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 26 publications
5
28
0
1
Order By: Relevance
“…Due to the small sample size of paired BRAF inhibitor samples from the BRAF inhibitor clinical trial, we could only identify a trend toward a correlation between CD40 + melanoma and patient survival, which warrants future trials to validate the role of CD40 + melanoma cells in treatment responses. Moreover, there is recent controversy around the microtubule-destabilizing activity of RGS preparations as to whether it is due to a contaminant or endogenous activity of RGS [ 67 , 68 ]. Of note, several clinical trials are investigating the effectiveness of combining microtubule inhibitors with ICB therapy in melanoma (NCT01827111, NCT00796991 and NCT02617849).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the small sample size of paired BRAF inhibitor samples from the BRAF inhibitor clinical trial, we could only identify a trend toward a correlation between CD40 + melanoma and patient survival, which warrants future trials to validate the role of CD40 + melanoma cells in treatment responses. Moreover, there is recent controversy around the microtubule-destabilizing activity of RGS preparations as to whether it is due to a contaminant or endogenous activity of RGS [ 67 , 68 ]. Of note, several clinical trials are investigating the effectiveness of combining microtubule inhibitors with ICB therapy in melanoma (NCT01827111, NCT00796991 and NCT02617849).…”
Section: Discussionmentioning
confidence: 99%
“…Initial findings described rigosertib as a multi-kinase signaling inhibitor with effects on PLK1, PI3K pathways, and the RAF-MEK-ERK pathway [7] , [30] , [31] , [32] , but the precise mechanism of action of rigosertib is still being debated [11] , [12] , [13] . Our results showing decreased pAKT (Ser473) and pERK1/2 (Thr202/Tyr204) levels indicate the involvement of the AKT and RAS signaling pathways in its mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…Rigosertib has also been proposed to function as a RAS mimetic by affecting the RAS-binding domain of RAS effector proteins, thereby inhibiting MEK-ERK signaling [10] . However, recent studies have shown that rigosertib functions as a microtubule-destabilizing agent [11] , therefore its precise mechanism(s) of action remain a matter of debate [12] , [13] . Nevertheless, rigosertib has shown anti-tumor effects in preclinical in vivo models of solid tumors including breast, pancreatic [6] , colorectal, and lung cancer [10] .…”
Section: Introductionmentioning
confidence: 99%
“…The stress MAP kinases phosphorylate components of the RAS pathway, including Raf family members and SOS1, a RAS guanine nucleotide exchange factor, which further decreases signaling through the RAS/RAF/MEK/ERK MAP kinase pathway (3). The mitotic stress induced by rigosertib may be due to the fact that rigosertib, or a degradation product of rigosertib, binds to an intradimer site between α-and β-tubulin in a manner similar to colchicine, which prevents microtubule growth (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%